Labour-law issues of the free movement of persons, services and capital - Senčur Peček, Darja (Anali PAZU HD, 2022)
Article deals with labour-law issues of three fundamental freedoms - free movement of people, services and capital. First of them is the notion of the employee in EU law. The definiton of the employee, developed by the Court of justice of the EU in connection with the free movement of workers, is more and more using in other fields of EU law. The second issue is the influence of freedom to establish and to provide services on the national collective labour law (especially on the right to strike and on the collective agreements). In connection with the free movement of the capital, the author deals with the necessity of protection of the employees in situation when capital structure of employer is changed.
Keywords: free movement of workers; notion of employee; freedom to establish; freedom to provide services; right to strikes